PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI TERHADAP KINERJA MANAJERIAL DIMODERASI KOMITMEN ORGANISASIONAL - Lia Suciati; Herlin Tundjung (Fakultas Ekonomi Universitas Tarumanagara, 2024)
This research aims at how the role of the role of budgetary participation, budget goal clarity and accounting controlon managerial performance, and the effect of organizational commitment implementation toward managerialperformance on State Civil Apparatus at North Jakarta District Court. Sample was selected using saturation samplingmethod and the valid data was 76 respondent. Data processing techniques using multiple regression analysis whathelped by SPSS program (Statistical Product and Service Solution) for Windows released 25. The results of this studyindicate that budgetary participation, budget goal clarity and accounting control have a positive and significantinfluence on manajerial performance, and organizational commitment increases influence budget goal clarity onmanagerial performance. The implication of this study is that managers can use budgetary participation, budget goalclarity and accounting control to improve managerial performance and to strengthen budget goal clarity onmanagerial performance can use organizational commitment.